The attitude and perceptions of doctors at Letaba Hospital towards family medicine: A qualitative study - Christian N. Saidiya; Gert J.O. Marincowitz; Doudou K. Nzaumvila; Tombo Bongongo; Indiran Govender (South African Family Practice)
Background: It was noted that family medicine (FM) was not used properly by doctors at Letaba Hospital. Anecdotally, misconceptions and misunderstandings about FM were reported. An exploration was recommended to understand the perceptions and attitudes of doctors at Letaba Hospital with regard to FM. Identifying doctors’ misconceptions and the possible reasons for mistaken beliefs about FM by other specialists could offer possible solutions.